Answer:
0 = 0 => Infinitely many solutions
Step-by-step explanation:
4x+7=x-2
-x -x
3x+7=-2
-7 -7
3x=-9
3 3 You divide -9 by 3.
x=-3
Your welcome
I: y=(1/2)x+5
II: y=(-3/2)x-7
substitution:
fancy word for insert the definition of one variable in one equation into the other
-> isolate a variable, luckily y is isolated (even in both equations) already
-> substitute y of II into I (=copy right side of II and replace y in I with it):
(-3/2)x-7=(1/2)x+5
-3x-14=x+10
-3x-24=x
-24=4x
-6=x
-> insert x back into I (or II):
y=(1/2)x+5
=(1/2)*(-6)+5
=-3+5=2
elimination: subtract one equation from the other to eliminate a variable, again y is already isolated->no extra work required
I-II:
y-y=(1/2)x+5-[(-3/2)x-7]
0=(1/2)x+5+(3/2)x+7
0=(4/2)x+12
-12=2x
-6=x
-> insert x back into I (or II):
y=(1/2)x+5
=(1/2)*(-6)+5
=-3+5=2
Answer:
Step-by-step explanation:
(12 dollars)/(8 cups) = (12/8 dollars)/cup = (1.5 dollars)/cup
21 dollars × (1 cup)/(1.5 dollars) = 21/1.5 cups = 14 cups